Concentration-dependent upregulation of CYP1A1 and CYP1B1 mRNA by phenobarbital in human peripheral blood lymphocytes - Sysa, Aliaksei; Ibrahim, Mgotir; Zhyvitskaya, Alena (Journal of the Belarusian State University. Ecology, 2025)
Cytochrome P450 enzymes CYP1A1 and CYP1B1, regulated by the aryl hydrocarbon receptor (AhR) pathway, play a critical role in xenobiotic metabolism and immunotoxicity. While phenobarbital is a known inducer of CYP450 enzymes, its concentration-dependent effects in human lymphocytes remain poorly characterized. Isolated human peripheral blood lymphocytes (PBLs) from healthy adult donors (n = 20) were exposed to phenobarbital (50 µM or 100 µM) for 5 h. CYP1A1/1B1 mRNA was quantified by qPCR (GAPDH reference; efficiency 90–110 %). A CFSE-based assay was used to assess cell viability at 72 h. Data are mean ± SEM; group differences were tested by one-way ANOVA with Tukey’s post hoc test; correlations by Pearson’s r. Phenobarbital at 50 µM increased CYP1A1 and CYP1B1 mRNA (3.42 ± 0.8- and 2.61 ± 0.5-fold vs control; both p < 0.01), whereas 100 µM elicited smaller induction (1.25 ± 0.2- and 1.21 ± 0.1-fold; both p < 0.05 vs control). The CFSE readout was reduced to 62 ± 7.1 % of control at 50 µM (p < 0.01) and was 88 ± 4.3 % at 100 µM (not significant vs control; p < 0.01 vs 50 µM). Induction of CYP1A1/1B1 negatively correlated with the CFSE readout (r = −0.85 and −0.82; both p < 0.001). Phenobarbital was associated with differential CYP1A1/CYP1B1 mRNA upregulation and reduced proliferation at the tested concentrations. These preliminary findings suggest potential concentration-related effects, warranting further mechanistic studies.